Knowledge and Attitudes Towards Breastfeeding Among Medical Students at Memorial University - Pendergast, Amanda L (Scholarship@Western, 2019)
Breastfeeding has many short term and long term health benefits to mothers and children, yet not all mothers in Canada initiate breastfeeding. Physicians’ support has been shown to improve breastfeeding rates, yet many physicians have poor knowledge and skills about breastfeeding. Improving breastfeeding education at an undergraduate level in medical school may lead to improved breastfeeding knowledge amongst physicians. This thesis explores medical students’ knowledge and attitudes towards breastfeeding at Memorial University. A previously validated questionaire was administered to first and second year medical students at Memorial University to examine their knowledge and attitudes towards breastfeeding. A descriptive qualitative study was conducted with breastfeeding educators at Memorial University to examine knowledge gaps within the breastfeeding curriculum. Medical students were found to have positive attitudes towards breastfeeding, yet limited knowledge. Students from rural areas had the highest attitude scores, whereas second year students had the highest knowledge scores. Breastfeeding educators noted many curriculum gaps in breastfeeding education, and provided suggestions to improve the curriculum. This study was the first to examine medical students’ knowledge and attitudes towards breastfeeding in Canada. The study was conducted in the Province of Newfoundland and Labrador, which has the lowest breastfeeding initiation rate in Canada. During the time of this study, undergraduate curriculum refinement was occurring at the medical school of Memorial University. Thus the findings of this study may lead to potential curricular improvements at Memorial University.